PENERAPAN INOVASI TEKNOLOGI BENIH KENTANG MENGGUNAKAN STEK PUCUK BEBAS VIRUS UNTUK MEWUJUDKAN KEMANDIRIAN PETANI MEMPRODUKSI BENIH KENTANG BERKUALITAS - Syarif Husen; Toto Suharjanto; Agus Eko Purnomo; Iqbal Ramadhani Fuadiputra; M. Zul Mazwan; Dwi Irawan; Aniek Iriany (Universitas Mataram, 2023)
The active land used for potato production in Pasuruan Regency is 3,000 ha, contributing 60% of the potato needs in East Java Province. The yield of potatoes from 3,000 ha is only 450 ha (15%) which is capable of producing 25 tonnes per ha, while the remaining 2.5 ha is only capable of producing 10-15 tonnes per ha. The difference in the productivity of potato plants is a result of the use of potato seeds that are not of good quality. The goal of this activity is that partners who are members of the Sari Rejo Farmer Group can produce potato seeds independently. As well as being able to distribute potato seeds widely to other areas. UMM established the Sari Rejo Farmer Group as a partner farmer group in the activity of producing Rooted Apical Cuttings potato seeds. The activity began with the acclimatization process to get the main plant, from the main plant the cuttings were carried out so that the seeds of rooted shoot cuttings were produced. The selection of these partners is based on the fact that the members have a high opportunity and interest in developing quality potato seeds. To overcome the existing problems, tutorial methods, training, and demonstration plots at partner locations are used, as well as partner group assistance. In its implementation, partners can provide land for demonstration plots and can maintain plants during the activity. The results so far, farmers have understood the potato seed plantlet acclimatization technology, so that mother plants are produced. Farmers have been able to produce seeds in the form of rooted apical cuttings independently so they can produce G2 class potato seeds in the open field. Partners can produce quality potato seeds for the needs of members and farmers outside the region.